Links Between Perceptions and Practices in Patient Education: A Systematic Review. (December 2019) - Roussel, Sandrine; Frenay, Mariane
Background . Two decades after "patient education" was defined by the World Health Organization, its integration in health care practices remains a challenge. Perceptions might shed light on these implementation difficulties. This systematic review aims to investigate links between perceptions and patient education practices among health care professionals, paying particular attention to the quality of practices in order to highlight any associated perception. Method . PubMed, PsycINFO, and Scopus were searched using the following search terms: "perceptions, " "patient education, " "health care professionals, " and "professional practices." PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were used. Results . Twenty studies were included. Overall findings supported the existence of links between some perceptions and practices. Links were either correlational or "causal" (generally in a single direction: perceptions affecting practices). Four types of perceptions (perceptions of the task including patient education, perceptions about the patient, perceptions of oneself as a health care professional, and perceptions of the context) were identified as being linked with educational practices. Links can although be mediated by other factors. Results concerning links should, however, be considered with caution as practices were mostly assessed by prevalence measurements, were self-reported and concerned exclusively individual education. When analyzing the quality of practices, the two retained studies highlighted their changing nature and the central role of perceptions with respect to the individual patient. Conclusions . This literature review led us to specify the quality criteria for further research: covering the entire spectrum of patient education, operationalizing variables, exploring specific practices, measuring the quality of practices, developing designs that facilitate causation findings, and considering a bidirectional perspective.